Providing Educational Videos to Improve Knowledge and Attitudes Towards Anemia Prevention For Teenage Females at SMPN 4 Madiun City - Yusmarisnasari; Riza Yuliawati; Amarin Yudhana; Ukik Agustina; Juvita Herdianty (Universitas STRADA Indonesia, 2024)
Based on the survey data on the prevalence of anemia in Indonesia by the Regional Health Research (Riskesdas) in 2018, it can be seen that children aged 15-24 years suffer from anemia by 32%. Adolescent girls are more susceptible to anemia due to the influence of a diet that does not meet balanced nutrition and the menstrual process every month. In Madiun City, based on anemia screening in grades 7 and 10 in the first quarter of 2024, the prevalence of anemia among adolescent girls was 39.67%. This shows that not all adolescent girls are aware of the dangers of anemia and efforts to prevent it. Therefore, a communication strategy is needed to prevent anemia in adolescent girls through health promotion media. This study aims to determine the effect of video media in increasing knowledge and attitudes towards preventing anemia among adolescent girls in SMPN 4 Madiun City. The design of this research is a pre-experimental one group pre-test and post-test design. The sample in this study were 7th and 8th grade students of SMPN 4 Madiun City, a total of 279 people using cluster random sampling. Data analysis in this study used the Wilcoxon test. The results of the study average score of knowledge about anemia prevention in adolescent girls with video media showed pretest (49.91), posttest (76.55) while the average score of attitude of adolescent girls showed pretest (70.75), posttest (79.59). The results of data analysis with the Wilcoxon test obtained the results of statistical tests of knowledge before and after intervention with a significance value of 0.000 <0.05 and the results of statistical tests of attitudes before and after intervention showed a significance value of 0.000 <0.05 which means that the p value of 0.000 <0.05 which means H0 is rejected, namely there are differences in knowledge and attitudes towards anemia prevention before and after providing anemia education video for adolescent girls at SMPN 4 Madiun City. Health promotion through video media is one of the communication strategies that can improve knowledge and attitudes about anemia prevention in adolescent girls. This research is expected to be developed until the intervention of the behavior of adolescent girls toward anemia prevention.